Cash Waqf Linked Deposito (CWLD): Implementasi Pada Bank Syariah - Hidayati, Atina; Inayah, Intan (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Indonesia has enormous waqf potential, one of which is cash waqf. The low level of literacy and socialization about waqf has led to the realization of waqf in Indonesia. According to the Indonesian Waqf Board, the potential of the waqf sector in Indonesia, the realization of cash waqf in 2023 will reach 1.22%. This shows that there is a very large gap between the potential and realization of cash waqf collection so that support and innovation in cash waqf products is needed. The existence of Cash Waqf Linked Deposits (CWLD), which was launched by Bank Jatim Syariah in 2023, provides waqf benefits in the social and educational fields. The benefits provided by CWLD are in the form of scholarships for students at universities and providing business capital to MSMEs. In this CWLD process, Sharia Banks act as Nadzir in collaboration with Sharia Financial Institutions Receiving Cash Waqf (LKSPWU) and customers act as Wakif. CWLD funds deposited to Nadzir have a minimum amount of 1 million rupiah and a minimum duration of 1 year. The returns from this CWLD instrument will later be given to the mauquf alaih, and the original waqf funds will be returned to the wakif or customer.